Opening Address - Zervas, Efthimios (E3S web of conferences, 2024)
The 5th International Conference on Environmental Design and Health which took place on October 18-20, 2024, in Athens, Greece, in a hybrid format (in situ and online), aimed to bring together researchers, academics and policy makers from around the world to discuss and share the latest innovations, research findings and practical applications in the field of Environmental Design, as well as health issues in relation to the environment.